The formation and breakdown of structured clots from whole milk during gastric digestion. Issue 10 (24th May 2016) - Ye, Aiqian; Cui, Jian; Dalgleish, Douglas; Singh, Harjinder
Abstract : The behaviour of milk fat globules in the coagula of unheated and heated (90 °C for 20 min) whole milk during gastric digestion was investigated using a human gastric simulator. Abstract : The behaviour of milk fat globules in the coagula of unheated and heated (90 °C for 20 min) whole milk during gastric digestion was investigated using a human gastric simulator. Structured protein clots were formed by a coagulation process that was driven by the action of the milk-clotting enzyme, pepsin, on the protein fraction of the whole milk. The fat globules in the milk appeared to be embedded in the clots as they formed. After clot formation, the different structures of the clots formed with unheated and heated whole milk led to different rates of protein hydrolysis by pepsin and resulted in the release of fat globules from the clots into the digesta; the release of fat globules was faster in the clots from the heated whole milk. Comparison of the rates of fat globule release from the clots and the rates of the reduction in fat-free matter in the clots showed that the release of fat globules from the clots from both unheated and heated milk was linearly dependent on the breakdown of the protein in the clots. Coalescence of fat globules appeared to occur in the gastric digesta and also within the protein.